Improving access to medicines by popularising generics: a study of 'India's People's Medicine' scheme in two districts of Maharashtra - Sonam Lavtepatil; Soumitra Ghosh (BMC, 2022)
Abstract Background In spite of being the 'pharmacy of the world', access to essential medicines for a large majority of Indians is constrained by both physical and financial reasons. According to an estimate, medicines account for 69% of household out-of-pocket spending on health care. To make quality generic medicine affordable, India's People's Medicine Scheme (Jan Aushadhi) was launched in 2008 and then revamped and rebranded as Pradhan Mantri Bhartiya Jan Ausadhi Pariyojana (PMBJP) in 2015. The current study focuses on the availability, affordability and acceptability aspects of PMBJP essential medicines. Methods We have used a mixed-methods approach, with the survey-based quantitative component supplemented by a qualitative component consisting of in-depth interviews (IDIs). The survey was conducted in 11 PMBJP pharmacies in Mumbai and Palghar. Data were gathered on the availability, stock-outs, price and affordability of 35 essential medicines and 2 consumables. Results Apart from the limited coverage of essential medicines and the significant presence of Fixed dose combinations (FDCs) in the PMBJP medicine list, the availability of surveyed essential drugs was also found to be low (47%) in PMBJP outlets. Across Mumbai and Palghar districts, around 50% and 42% of medicines were found to be out of stock for the period of 3-6 months respectively. The cost of generic medicines of PMBJP outlets for treating various conditions range from 0.01 days' wages to 0.47 days' wages for the lowest paid unskilled worker in Maharashtra. Conclusions The study findings show that PMBJP's unbranded generics offer great opportunities for substantial cost savings. But, in order to fully realise the potential of this scheme, some policy actions are urgently required. First, the PMBJP drug list must include all essential drugs that feature in NLEM. Second, BPPI should procure only those drugs that pass the bioequivalence test. Third, compulsory de-branding of generics should be done in a phased manner. Fourth, PMBJP's medicine procurement and distribution policies must be reviewed to address the supply chain issues. Moreover, there is a need for major pharmaceutical policy reforms to promote generic medicines in a big way. Regulations to support mandatory generic prescribing and generic substitution by pharmacists are needed.